ERANAN CAMAT DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT (SUATU STUDY DI KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA) - RACHMAN, ISMAIL (JURNAL ADMINISTRASI PUBLIK, 2017)
One of the government entity is to give direct and indirect service to the society in the district orKecamatan. As the government sub-system in Indonesia, Kecamatan has the strategic position to playthe functional role in governance, service, administration, development also for the society itself.Camat has important role in implementing the society’s empowerment. The empowerment model bythe government is to give positive impact in business development and economic empowerment for thesociety. Through certain program, so many benefit can be obtained by the society in order to createsociety’s improvement in culture, social and economic in Likupang Timur.Keywords; The role of Sub-district Head, Community Empowerment